Total Transfemoral Percutaneous Endovascular Aortic Arch Repair Using 3-Vessel Inner Branch Stent-Graft - Emanuel R. Tenorio, MD, PhD; Thanila A. Macedo, MD; Laura Ocasio, MD; Marina Dias Neto, MD, PhD; Guilherme B. Barbosa Lima, MD; Aidin Baghbani-Oskouei, MD; Anthony L. Estrera, MD; Abhijeet Dhoble, MD; Shao Feng Zhou, MD; Gustavo S. Oderich, MD (JACC: Case Reports, 2022)
Endovascular repair has been introduced to decrease the morbidity and mortality associated with open surgical repair of aortic arch pathology. We illustrate total percutaneous transfemoral approach with a 3-vessel inner branch stent-graft to treat aortic arch aneurysm. (Level of Difficulty: Advanced.)